The Change of Motives to Become and to be a~Party Member. An Empirical Analysis of the German Party Membership Studies 1998, 2009 and 2017 - Yvonne Lüdecke; Markus Klein; Frederik Springer; Philipp Bernhold; Lisa Czeczinski; Bastian Schmidt (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
In this paper, the thesis is put forward that selective outcome incentives for party membership gain relevance over time. Two possible mechanisms are identified as the cause of this increase in importance: a~supply-side mechanism based on processes of societal change that took place through generational succession and a~demand-side mechanism focusing on shifts in the self-image and organizational structure of political parties. The supply-side mechanism should lead to changes in the motives of potential members, whereas the demand-side mechanism alters the incentives potential and current members are exposed to. The empirical analyses are based on the German Party Membership Studies of 1998, 2009 and 2017. These three studies are nationwide representative surveys of the members of the following six parties: Christian Democratic~Union (CDU), Christian Social Union (CSU), Social Democratic Party of Germany (SPD), Free Democratic Party (FDP), Alliance90/The Greens (Bündnis90/Die Grünen), and The Left (Die Linke). Within the German Party Membership Studies, both the motives for joining the party and the current membership motives are surveyed. Empirically, it is shown that there is indeed an increase in the importance of selective outcome membership motives over the period under study. The mechanisms behind this increase in importance are investigated using multivariate Age-Period-Cohort (APC) models based on the cumulated data of the German Party Membership Studies. These analyses are based on a~total of nearly 30,000 cases. The results of the APC analyses are largely consistent with the supply-side explanation of the increased importance of selective outcome motives for party entry and membership. The demand-side explanation is only partially confirmed.
Keywords: 300; General Incentives Model; APC analysis; Political ambition; Selective outcome incentives; Candidate recruitment; General-Incentives-Model; APK-Analyse; Politische Ambitionen; Selektive ergebnisbezogene Anreize; Kandidatenrekrutierung